Decision Making System for Village Apparatus Selection in Pinang Raya District, North Bengkulu Regency - Ujang Juhardi; Maulana Fajar Alamsyah (Jurnal Komputer, Informasi dan Teknologi, 2022)
The Village Apparatus is one of the important parts in the framework of running the Village government as referred to in the Law of the Republic of Indonesia No. 6 of 2004. The appointment of Village apparatus is carried out by the Village Head as stated in the Law of the Republic of Indonesia Number 6 of 2014. The problem is that the selection of village apparatus is still done manually or has not been systemized and has the opportunity to cause errors in the selection of village apparatus. For this reason, it is necessary to have a system that can make it easier for village heads to find references for systematically selecting village officials. Decision Support System (DSS) is an interactive computer-based system, which helps decision makers utilize data and models to solve unstructured and semi-structured problems (Turban, Liang and Aronson, 2005). On this basis, researchers are interested in conducting research with the title "Decision Support System for Village Apparatus Selection in Pinang Raya District, North Bengkulu Regency" with the calculation method that will be used is Simple Additive Weight (SAW). It is hoped that this system can help facilitate the Village Head in determining the best candidate for his Village Apparatus.